The personal data protection mechanism in the european union - Syroid , Tetiana L.; Kaganovska , Tetiana Ye.; Shamraieva , Valentyna M.; Perederiі , Оlexander S.; Titov , Ievgen B.; Varunts , Larysa D. (Seoul : Soong-Sil University, 2021)
The adoption of the General Data Protection Regulation (EU) 2016/679 transformed approaches and concepts to the implementation of the personal data protection mechanism in the European Union. Within the EU, almost all countries have adapted a new protection mechanism, which requires a study of the specifics of its use. The article intends to assess the legal provisions of the current mechanism of personal data protection in the EU. The author studied the mechanism of personal data protection under the General Data Protection Regulation (EU) 2016/679 (GDPR) based on the concept of contextual integrity and analysis of EU legislation on personal data protection. The scientific publications for 2016-2020 were reviewed for the formation of ideas of a new personal data protection mechanism in the EU, informative and transparent analysis of legal provisions. The article notes that the personal data privacy and protection is increasing, there is an ongoing unification of the legal status of personal data protection and the formation of a digital market for dissemination, exchange, control, and supervision of data. Cross-border cooperation is part of the personal data protection mechanism. The author proved that the GDPR has changed approach to personal data protection: the emphasis is now shifting to the formation of a digital market, where the EU’s role in ensuring regulation is crucial. The article identifies the emergence of a new protectionist legal system and strengthening of legal provisions regarding privacy. This legal system needs unification and harmonization in accordance with national legislation, is territorially fragmented and differentiated within the EU.
Keywords: LAW/JURISPRUDENCE; ersonal dat; personal data protection; GDPR; data protection authorities in EU; GDPR implementation in EU